2010
DOI: 10.1248/bpb.33.1650
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Functional Induction of the Quinone Reductase and Cytochrome P450 1A1 by Youngiasides via Nrf2-ARE and AhR-XRE Pathways

Abstract: Cancer chemoprevention is defined as the use of phytochemicals (naturally occurring compounds or their synthetic derivatives) from dietary foods or natural products to inhibit, delay or reverse carcinogenesis or prevent the development of cancer.1,2) The important strategy of cancer chemoprevention aims to reduce the risk of cancer through modulation of detoxification enzymes involved in metabolic activation. The detoxification/excretion of carcinogens is one of the representative mechanisms of action of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…[13][14][15] We recently reported that youngiasides A, B, and C isolated from CD could induce detoxification enzymes, quinone reductase and CYP 1A1, through the activation of Nrf2 and the aryl hydrocarbon receptor (AhR). 16 We also recently reported that CD had a protective effect in HepG2 cells against tert-butyl hydroperoxide, a strong inducer of oxidative stress, by increasing the glutathione level. 12 In the present study, we investigated whether CD extract may protect the liver against alcohol in vivo and whether there is potential for the development of a dietary supplement to improve liver function against chronic alcohol consumption.…”
Section: Introductionmentioning
confidence: 80%
“…[13][14][15] We recently reported that youngiasides A, B, and C isolated from CD could induce detoxification enzymes, quinone reductase and CYP 1A1, through the activation of Nrf2 and the aryl hydrocarbon receptor (AhR). 16 We also recently reported that CD had a protective effect in HepG2 cells against tert-butyl hydroperoxide, a strong inducer of oxidative stress, by increasing the glutathione level. 12 In the present study, we investigated whether CD extract may protect the liver against alcohol in vivo and whether there is potential for the development of a dietary supplement to improve liver function against chronic alcohol consumption.…”
Section: Introductionmentioning
confidence: 80%
“…Isolation of chemical constituents ( Figure 1A) from Y. denticulatum was performed as previously described. 19 Cell Culture and UVB Irradiation. HaCaT and HDF cells were purchased from the American Type Culture Collection (Manassas, VA, USA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The cellular distribution of b-catenin was evaluated by an immunofluorescence assay using confocal microscopy (Leica, Wetzlar, Germany) as previously described [21]. In brief, HCT116 (7 Â 10 3 cells/well) cells were seeded onto glass cover slips in 24-well plates and were incubated for 24 h prior to treatment.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%